2023
DOI: 10.3390/antiox12071400
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Different Molecular Weights of Purslane (Portulaca oleracea L.) Aqueous Extract on DSS-Induced Ulcerative Colitis in Mice

Abstract: Purslane, a common wild vegetable, contains active substances with various biological functions. However, its effects have been under-investigated in ulcerative colitis (UC). Therefore, this study investigated the therapeutic effects of purslane macromolecular (POEM) and small molecular extracts (POES) on dextran sulfate sodium (DSS)-induced UC in mice. Membrane separation was used to obtain extracts of different molecular weights, and their compositional differences were compared using liquid chromatography–m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Studies have shown that SCFAs can exert anti-inflammatory effects by regulating immune cell function and cytokine secretion and can also prevent colon carcinogenesis [37]. Conversely, LPS can exacerbate inflammatory responses and oxidative stress and affect intestinal barrier function [38]. This study found that WPH intervention could rescue the reduction in the level of SCFAs induced by DSS and increase the level of LPS, and the effect was more pronounced with high doses of WPH.…”
Section: Effect Of Wph Intervention On Lps and Scfas In Mice With Dss...mentioning
confidence: 50%
“…Studies have shown that SCFAs can exert anti-inflammatory effects by regulating immune cell function and cytokine secretion and can also prevent colon carcinogenesis [37]. Conversely, LPS can exacerbate inflammatory responses and oxidative stress and affect intestinal barrier function [38]. This study found that WPH intervention could rescue the reduction in the level of SCFAs induced by DSS and increase the level of LPS, and the effect was more pronounced with high doses of WPH.…”
Section: Effect Of Wph Intervention On Lps and Scfas In Mice With Dss...mentioning
confidence: 50%